LINGVO-DIDACTIC BASIS OF CONTROLLING OF THE COMMUNICATIVE-ORIENTED SPEECH SKILLS - Kurbanova, Marguba (Innovative Development in Educational Activities, 2023)
In this article the author of the work also dwells on the concept that there are two types of oral communicative tests in the form of interview and in the form of role playing game in the modern lingvo-didactic testing and the choice of this and that form always depends on purpose, objects and stage of testing and teaching. The notion “an oral communicative test in the form of interview” is carried out from linguistics, methods of teaching foreign languages and physiology point of view in the article. The basic components of foreign communicative competence are indicated in the works of Uzbek and foreign scientists, and the new component parts are added that are actual for a specialist of linguistic institute of higher education.